Respuesta :

Answer:

(6, 4 )

Step-by-step explanation:

Given the 2 equations

2x - 6y = - 12 → (1)

x + 2y = 14 → (2)

Multiplying (2) by - 2 and adding to (1) will eliminate x

- 2x - 4y = - 28 → (3)

Add (1) and (3) term by term to eliminate x

- 10y = - 40 ( divide both sides by - 10 )

y = 4

Substitute y = 4 into either of the 2 equations and solve for x

Substituting into (1)

2x - 6(4) = - 12

2x - 24 = - 12 ( add 24 to both sides )

2x = 12 ( divide both sides by 2 )

x = 6

solution is (6, 4 )

ACCESS MORE